Effect of doping and vacancy defect on the sensitivity of stanene toward HCN. (3rd April 2022) - Yan, Shumin; Zhou, Qingxiao; Ju, Weiwei; Li, Xiangyang
Abstract : The adsorption behaviour of HCN molecule on a modified stanene substrate is investigated using first-principles calculation. The large adsorption distance, small adsorption energy and low charge transfer indicated that HCN molecule exhibits a weak physical adsorption mechanism on stanene. After introducing dopant and vacancy defects in the stanene substrate, the adsorption mechanism of HCN transformed into chemisorption. The significantly increased adsorption energy suggested that the interaction between the doped substrate and HCN was enhanced. Interestingly, the Cr-doped system not only exhibited a large charge transfer but also an intense magnetic performance. Our calculation results may provide useful information for fabricating stanene-based sensors. Highlights The adsorption of HCN on intact stanene is physical adsorption. The adsorption of HCN on vacancy defect stanene is chemisorption. The Cr doped vacancy-defected stanene is suitable for the HCN gas sensor. GRAPHICAL ABSTRACT: UF0001